The Influence of Extreme Heat on Police and Fire Department Services in 23 U.S. Cities. (6th November 2020) - Williams, Augusta; McDonogh‐Wong, Larissa; Spengler, John D.
Abstract: Recent research suggests that extreme heat affects the demand for emergency services, including police and fire department incidents. Yet there is limited understanding of impacts across U.S. cities, with varying population sizes, and between different climates. This study sought to examine the daily utilization of police and fire department services, during hot days in 23 U.S. cities representing six climate zones using relative risk (RR) and time series analyses of daily police and fire department incidents. The warm season analyses utilized three temperature metrics: daily maximum temperature (TMAX ), daily maximum heat index (HIMAX ), and the preceding daily minimum temperature (TMIN ). Across these cities, the RR of police department incidents on days where TMAX was at or above the 95th percentile significantly increased within a range from 3% (95% confidence interval [CI]: 0.3%, 6.3%) to 57% (95% CI: 24.5%, 89.7%), compared with a nonhot day. At the same temperature thresholds, the RR of fire department dispatches increased from 6% (95% CI: 3.0%, 8.6%) to 18% (95% CI: 15.2%, 21.6%). These results remained consistent across temperature metrics and consecutive days of extreme heat. The estimated effects of daily maximum temperature, daily maximum heat index, and daily minimum temperature were nonlinear for police and fire department incidents across all cities. These findings inform climate change adaptation strategies, preparing budgets and personnel for emergency agencies to ensure resilience as periods of extreme heat increase in frequency, severity, and duration. Plain Language Summary: Extreme heat has previously been found to increase violent crime, medical emergencies, and traffic accidents. However, the relationship between heat and increased demand for overall police services and fire department incidents is less understood. This study looks at 23 cities across the United States that vary in population, geography, and climate, to see how extreme heat influences daily demand for police and fire department services. City specific analyses can directly inform community managers on how to plan for future emergency service needs. We found that on days where the temperature was at or above the 95th percentile of historical temperatures for that month, police and fire departments were significantly more likely to experience higher incident numbers than on nonhot days in 7 of 17 (police) and 11 of 14 (fire) cities. The estimated effects of daily maximum temperature, daily maximum heat index, and daily minimum temperature were nonlinear for police and fire department incidents across all cities. These findings are critical to ensuring the resilience and capacity of emergency services and emergency service workers, so they can meet the needs of their citizens as periods of extreme heat become more common. Key Points: Forty‐one percent (79%) of cities had higher relative risk of police (fire) department dispatches on days when the TMAX > = 95th percentile The estimated effects of daily TMAX, daily HIMAX, and daily TMIN were nonlinear for police and fire department incidents across all cities These findings can inform climate change adaptation strategies to enhance the resilience of budgets and first responders in a hotter world